2009
DOI: 10.1002/anie.200902934
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic Mesostructured Alloys: Design of Ordered Mesostructured Alloys with Multicomponent Metals from Lyotropic Liquid Crystals

Abstract: Magnets made to order: Highly ordered multicomponent mesostructured alloys with controllable compositions have been synthesized [see TEM image and electron diffraction patterns (inset)]. The saturation magnetization of the alloys can be controlled by changing the ratio of metal components. New functions that are not found in a single metal system can be realized by alloying, thus opening up a range of new magnetic applications for these materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 72 publications
0
42
0
Order By: Relevance
“…Block copolymers are traditionally utilized as direct templates under ultra-high concentration, namely, lyotropic liquid crystals (LLC), [37] for the synthesis of metal-based mesoporous materials. [38,39] The proposed approach is carried out under very low block copolymer concentration, which is distinctly different from the traditional LLC strategy. The presented method provides a new avenue for the creation of alloy nanomaterials with dendritic shape, which greatly contributes to the further development of novel intermetallic alloy nanodendrites with more complex compositions.…”
Section: Resultsmentioning
confidence: 99%
“…Block copolymers are traditionally utilized as direct templates under ultra-high concentration, namely, lyotropic liquid crystals (LLC), [37] for the synthesis of metal-based mesoporous materials. [38,39] The proposed approach is carried out under very low block copolymer concentration, which is distinctly different from the traditional LLC strategy. The presented method provides a new avenue for the creation of alloy nanomaterials with dendritic shape, which greatly contributes to the further development of novel intermetallic alloy nanodendrites with more complex compositions.…”
Section: Resultsmentioning
confidence: 99%
“…The strongly size-related properties of nanomaterials offer unexpected and unprecedented behaviours, which bears great potential for innovative technological applications12345. Magnetic nano materials have attracted intensive research interest among magnetism researchers for decades due to their huge potential in technological applications, both in magnetic applications such as recording technology and in multidisciplinary exploration such as biology and medicine6789. The large specific surface area induces novel magnetic behaviour, such as exchange bias in pure ferromagnetic, ferrimagnetic, and antiferromagnetic nanoparticles10.…”
mentioning
confidence: 99%
“…4,33,34 An impressive recent example is the synthesis of multicomponent mesoporous alloys (Fe, Co, Ni,) with adjustable compositions by changing the ratio of metal salts dissolved in the aqueous domains of a non-ionic surfactant (Brij 56). 35 The results revealed that the ordering of binary Ni-Co mesostructures decreased with increasing Co content in the alloys. Furthermore, the tuneable ratio of Ni/Co in these mesostructures led to the controllable saturation magnetization.…”
Section: 1 Template Synthesismentioning
confidence: 91%